Impact Of Accountability, Public Transparency, And Internal Oversight Functions On The Performance Of The Regional Government Of Bengkulu District Central - Detta Rizka Maharani; Fadli Fadli (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The study aims to investigate the influence of accountability, public transparency, and internal supervision responsibilities on the performance of the Bengkulu District Regional Government in relation to the Central District Development Unit. This investigation conducts quantitative research by administering questionnaires to each SKPD and employing survey methodologies to gather data. The method of purposive sampling is employed to select samples according to predetermined criteria. In the district of Bengkulu Central, the sample was composed of 40 respondents who were selected from 40 Working Units of Regional Devices (SKPD). The methodology utilized is double linear regression analysis. This study's results suggest that the regional government's operations are significantly influenced by both internal supervision and accountability responsibilities. However, regional administration's efficacy is minimally affected by the degree of public transparency. It is evident from the test results that the Regional Government's performance is not guaranteed to be improved by the presence of Public Transparency. Nevertheless, the potential enhancement of the regional government's efficacy could be positively influenced by the implementation of transparent and internal monitoring systems within the local administration, which are accountable to the public.